Effect of AL2O3 and TiO2 nanoparticles on aquatic organisms. Issue 1 (October 2015) - Gosteva, I; Morgalev, Yu; Morgaleva, T; Morgalev, S
Abstract: Environmental toxicity of aqueous disperse systems of nanoparticles of binary compounds of titanium dioxides (with particle size Δ50 =5 nm, Δ50 =50 nm, Δ50 =90 nm), aluminum oxide alpha-forms (Δ50 =7 nm and Δ50 =70 nm) and macro forms (TiO2 Δ50 =350 nm, Al2 O3 A50 =4000 nm) were studied using biological testing methods. The bioassay was performed using a set of test organisms representing the major trophic levels. We found the dependence of the toxic effect concentration degree of nTiO2 and nAl2 O3 on the fluorescence of the bacterial biosensor "Ekolyum", the chemotactic response of ciliates Paramecium caudatum, the growth of unicellular algae Chlorella vulgaris Beijer and mortality of entomostracans Daphnia magna Straus . We revealed the selective dependence of nTiO2 and nAl2 O3 toxicity on the size, concentration and chemical nature of nanoparticles. The minimal concentration causing an organism's response on nTiO2 and nAl2 O3 effect depends on the type of the test- organism and the test reaction under study. We specified L(E)C50 and acute toxicity categories for all the studied nanoparticles. We determined that nTiO2 (Δ50 =5 nm) belong to the category «Acute toxicity 1», nTiO2 (A50 =90 nm) and nAl2 O3 (Δ50 =70 nm) – to the category «Acute toxicity 2», nAl2 O3 (Δ50 =7 nm) – to the category «Acute toxicity 3». No acute toxicity was registered for nTiO2 (Δ50 =50 nm) and macro form TiO2 .